The inheritance of cryptocurrency and cryptowallet profiles - Puskás, Tamás (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2026)
The digitalisation is one of the most important aspect in the twenty-first century, and thus huge amount of personal data is being accumulated about each person day-by-day. It is still a debate in many countries who we could view these datasets after the passing of the person and whether the heirs should have the right to access and maintain the dignity, memory of the deceased. One of the element of the so-called ’digital inheritance’ would be cryptocurrency which contains an enormous economic potential. This study explores and highlights the reality, the possibility of the inheritance of cryptocurrency, also the wallets, especially the online platform accounts, which these assets are stored in, in a European context through the already existing cases in the world.